Financial austerity in Iraq causes and effects on economic performance indicators - داود سمير سهام; علي منعم حسين (Journal of Economics and Administrative Sciences, 2019)
Abstract: The Iraqi economy faces complex economic challenges that threaten the prospects for growth and stability in the short and medium term, The decrease in oil revenues on which Iraq is based in financing its total expenditure, both operational and investment, led to the emergence of a deficit in the government budget, As the global oil price crisis affected the revenues of the Iraqi government negatively, especially as this negative impact coincided with the increase in military spending resulting from Iraq’s war against terrorism, Which led to the Iraqi government to implement austerity measures were to reduce public spending on several projects, which are less important compared to projects that are of great importance in the economy, the application of austerity policy led to negative effects on indicators of economic performance was a decrease in public spending And the increase in taxes that led to a decrease in the income prepared for spending by individuals and thus a decrease in aggregate demand, The Central Bank’s adoption of a tight monetary policy through the reduction of loans granted to commercial banks led to a decrease in cash reserves at commercial banks, which led to a reduction in total loans granted to projects owned by individuals and consequently led to a decline in the level of economic activity.